Antioxidants in treatment of kraurosis vulvae - E. A. Kiseleva; A. Sh. Makhmutkhodzhaev; G. A. Mikheenko (Фундаментальная и клиническая медицина)
Aim. To study impact of ethylmethylhydroxypyridine succinate, an antioxidant, on the efficacy of photodynamic therapy (PDT) of kraurosis vulvae (vulvar lichen sclerosus).Materials and Methods. The study enrolled 90 patients with kraurosis vulvae who were randomised into 3 groups receiving: 1) PDT and ethylmethylhydroxypyridine succinate 1 week after the start of the PDT for 1 month; 2) PDT without ethylmethylhydroxypyridine succinate; 3) low-level laser therapy on the perineal region. Clinical manifestations of kraurosis vulvae were dynamically assessed before the treatment and 1, 6, and 12 months post treatment. The severity of vulvar itching was evaluated using visual analogue scale. LS-A index was calculated to determine the disease activity, whilst LS-S index was applied to quantify the affected vulvar area.Results. PDT demonstrated higher therapeutic efficacy in treatment of kraurosis vulvae than low-level laser therapy. Addition of ethylmethylhydroxypyridine succinate to the treatment protocol improved the results of PDT, as remission of vulvar itching within 12 months was achieved in 73% of patients who received PDT in conjunction with ethylmethylhydroxypyridine succinate and only in 47% of participants receiving PDT alone (p = 0.042). One month post treatment, the intensity of itching according to visual analogue scale was 2.0 points in patients who received combined treatment and 4.5 points in those receiving PDT alone (p < 0.001). Vulvar epithelialization also occurred earlier in patients receiving combined treatment (48 ± 5 days versus 54 ± 3 days in those receiving PDT alone, p < 0.001). Upon 12 months of observation, disease activity and affected vulvar area were significantly lower in patients receiving combined treatment (LS-A 4.0; LS-S 1.0) as compared to the PDT alone (LS-A 6.5; LS-S 3.0, p = 0.004 and < 0.001, respectively).Conclusion. Addition of ethylmethylhydroxypyridine succinate to photodynamic therapy demonstrated high efficacy against kraurosis vulvae and can be recommended for its treatment.